PENINGKATAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN IPA DENGAN STRATEGI PEMBELAJARAN INKUIRI - Libriawati, Resti; Silvinia, Silvinia; Muhammadi, Muhammadi (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2014)
Abstract The background of this research is the low learning results of the students caused by teacher’s less maximal effort in using the strategies in teaching and learning process. The purpose of this research is to describe the improvement of Science learning results with inquiry learning strategy in Grade VI of Elementary School 01 Nan Sabaris. This research is a Class Action Research which uses qualitative and quantitative approach. The data is obtained from observation and test sheets. The research results in each cycles that have been done shows the improvement on  Lesson Plan assessment by 72.00% to 90.26%, on teacher’s performance aspect bby 72.92% to 87.50%, on students’ aspect by 68.75% to 83.33%, and on learning results aspect by 71.17% to 84.44% in average. Thus, inquiry learning strategy is able to improve students’ learning results in Science learning in Grade VI of Elementary School 01, Nan Sabaris.  Key words: learning result, inquiry learning strategy